From separation between state and religion to religion-freeing state the changing faces of secularism in Turkey - Mohd Roslan, Mohd Nor; Muhammad Khalis, Ibrahim (2023)
From the very beginning, the establishment of modern Turkey adhered to the secularisation process, namely to separate the state from religious influence. Although religion has been marginalised, Islam remained a major societal force in Turkey. This scenario raises some questions: What is the idea of Turkish secularism? How can religion possess influence in the context of Turkey as a secular state? What is the form and orientation of secularism in Turkey? Therefore, this study aims to answer these questions by scrutinising the idea, history, and orientation of secularism in Turkey. To fulfil this objective, we scrutinised documents and previous studies related to Turkish secularism. Then, the idea of Turkish secularism was critically and chronologically analysed from the early time it was implemented up to the present time to assume its orientation. In the early time, Turkish secularism did not solely separate the state from religion, but perceived that the state should control religion as well. Its assertive nature has forced the emergence of a more liberal version of secularism, which treats the idea of separation between the state and religion according to the notion of democracy, and hence, freed religion from the strict, tutelary state. Secularism in Turkey under the present regime is different from before, as religious (Islamic) manifestation is increasingly visible in public spaces even though the state remains secular. We argue that the present Turkish secularism can become a “model” for other Muslim countries that are still dealing with the conflict regarding the religion-state relationship.